Svordomar i ett lexikografiskt perspektiv - Stroh-Wollin, Ulla (Nordiske Studier i Leksikografi, 2012)
During the work on a list of swear words found in Swedish dramas from the 18th, 19th and 20th centuries, it became clear that the art of swearing has hitherto not received much attention from Swedish lexicographers. An especially intriguing challenge is how to describe the more or less conventionalized phrases and constructions of which swear words are a part. The specific contribution of a swear word phrase to the meaning of an utterance is not always obvious and requires a very careful analysis. In some cases, phrases that look quite different are pragmatically and syntactically interchangeable – sometimes fully so, sometimes partly. On the other hand, even minor differences between two phrases may have a considerable impact on their meaning. Thus, the lexicographer’s challenge, besides explaining every single expression, may include accounting for the relations between different words and phrases as well. Further, information on the syntactic functions that swear words and swear word phrases can have is normally not included in dictionaries, but may in fact be very valuable to their users. However, several syntactic functions are more or less fulfilled exclusively by swear words. In these cases, grammatical labels are missing, swear words being neglected even by traditional grammar.